2012
DOI: 10.1111/j.1365-277x.2012.01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of dietary intentions in pregnancy

Abstract: Lack of effects for barriers, threat and subjective norms may indicate that pregnant women discount barriers to health-promoting behaviour, understand the threat posed by unhealthy eating and perceive social approval from others. Dietary change interventions for pregnant women should emphasise likely positive outcomes for both mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…Attitudinal data relating to diet were comparable to a population sample of pregnant women [12]. The intervention did not achieve any reduction in perceived barriers, but despite this, important dietary changes were achieved which may infer low levels of self efficacy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Attitudinal data relating to diet were comparable to a population sample of pregnant women [12]. The intervention did not achieve any reduction in perceived barriers, but despite this, important dietary changes were achieved which may infer low levels of self efficacy.…”
Section: Discussionmentioning
confidence: 82%
“…Prior to embarking on a large randomised controlled trial (RCT) and in accordance with UK Medical Research Council Guidance for development of a complex intervention [10], we first explored the theoretical basis for an intervention in obese pregnant women [5,6,11,12], leading to development of a novel intervention (Phase 1). We now report on Phase 2, an exploratory trial to determine whether this intervention achieved the changes in dietary and physical activity behaviours anticipated, and to undertake a process evaluation of every aspect of fidelity of the intervention and the protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps older mothers did not perceive that they needed to decrease their sugar consumption, despite receiving education and setting goals to reduce added sugar consumption. Gardner et al found that pregnant women who perceived their current intake to be excessive were significantly more likely to intend to eat less high-sugar foods than those who believed their intake to be adequate (Gardner et al, 2012). Further research in similar populations is needed to better understand how age might influence effectiveness of interventions aimed at dietary change in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women who already consume a diet with excess fat and sugar content are also more likely to intend to lower the intake of these foods. 9 A recent review of 10 studies that tried to define the most effective components of successful interventions for limiting gestational weight gain found no evidence to favour one behavioural technique over another, but there was some suggestion that interventions were more likely to succeed in non-smokers and if started early in pregnancy. 10 The lack of detail and standardised reporting of the psychological theory underpinning the behavioural change or the specific techniques used in the interventions were notable.…”
Section: Editorialsmentioning
confidence: 99%